Penggunaan Desikan Abu Dan Lama Simpan Terhadap Kualitas Benih Jagung (Zea mays L.) Pada Penyimpanan Ruang Terbuka - M. K Lesilolo; Jacob Patty; N. Tetty (Faculty of Agriculture, Pattimura University, 2012)
This study was aimed to determine the proper dose of ash desiccant on maize seed stored for 30, 60 and 90 days. The design used was a Completely Randomized Factorial Design, with two factors and three replications. The first factor was desiccant dose (D) : Do = 0 % (control), D1 = 5 % (12.5 g of seed weight), D2 = 10% (25 g of seed weight), D3 = 15 % (37 g of seed weight), D4 = 20 % (50 %g of seed weight), D5 = 25 % (62.5 g of seed weight). The second factor was length of storage (S) : S1 = 30 day storage, S2 = 60 day storage and S3 = 90 day storage. The result show that use of desiccant only gave effect on the water content of seeds (12.31 %) and speed of seed growth vigor parameters (24.84 %). Use of desiccant in 90 day storage were able to maintain water content of seeds (12.43 %), seed germination viability parameter (100 %), and vigor of seeds, which consisted of seed growth simultaneity (66.77 %) and seed growth speed (28.71 %). The interaction between the use off ash desiccant and the length of storage had no effect on viability and vigor of maize (Zea mays L) seeds but had an effect on their water content after storage (12.73%).